Visible-Light-Responsive Antibacterial Property of Boron-Doped Titania Films - Ming-Show Wong (Catalysts, 2020)
Pure titanium dioxide TiO2 photocatalytic substrates exhibit antibacterial activity only when they are irradiated with ultraviolet light, which comprises high-energy wavelengths that damage all life. Impurity doping of TiO2-related materials enables visible light to stimulate photocatalytic activity, which enhances opportunities for TiO2 to be used as a disinfectant in living environments. Boron-doped TiO2 displays visible-light-responsive bactericidal properties. However, because boron-derived compounds also exert notable antibacterial effects, most reports did not clearly demonstrate the extent to which the bactericidal property of boron-doped TiO2 is contributed by visible-light-stimulated photocatalysis. In addition, TiO2 thin films have considerable potential for applications in equipment that requires sterilization; however, the antibacterial properties of boron-doped TiO2 thin films have been examined by only a few studies. We found that boron-doped TiO2 thin films displayed visible-light-driven antibacterial properties. Moreover, because boron compounds may have intrinsic antibacterial properties, using control groups maintained in the dark, we clearly demonstrated that visible light stimulated the photocatalysis of boron-doped TiO2 thin films but not the residue boron compounds display antibacterial property. The bactericidal effects induced by visible light are equally potent for the elimination of the model organism Escherichia coli and human pathogens, such as Acinetobacter baumannii, Staphylococcus aureus, and Streptococcus pyogenes. The antibacterial applications of boron-doped TiO2 thin films are described, and relevant perspectives discussed.